The Effectiveness Interpersonal Communication Increasing Success of Pokdarwis Arumsari - Prasetyo, Agus Subhan; Nurul Balqis Qurratu Aini; Anisa Nurina Aulia; Dwiyana Anela Kurniasari; Wengki Ariando (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Organizing that involves the community is one of the factors that can determine the success of implementing tourism village activities. One of the tourism village managers whose organization involves the community is the Arumsari Tourism Awareness Group (Pokdarwis) in the Pandansari Tourism Village. To achieve the success of Pokdarwis Arumsari, it is necessary to have effective interpersonal communication between members, so, this study aims to analyze the effectiveness of interpersonal communication and its influence on the success of Pokdarwis Arumsari. The research location was conducted in Pandansari Village, Batang Regency, Central Java. The research method uses the case study method on all members of Pokdarwis Arumsari totaling 37 people as the respondents. Data collection techniques are closed interviews, observation, and literacy studies. Then analyzed by using Partial Least Square (PLS). The effectiveness of interpersonal communication and the success of Pokdarwis Arumsari are included in the high category with a percentage score of 81.2% and 79.2%, respectively. The value of the path coefficient is 0.859, the direction of the relationship between the effectiveness of interpersonal communication on the success of Pokdarwis Arumsari is positive, there is an effort to increase the effectiveness of interpersonal communication within the group, the success of Pokdarwis will increase. The results of the analysis show that the effectiveness of interpersonal communication can explain 73.9% of the success of Pokdarwis Arumsari. Pokdarwis Arumsari has a good and positive effect on interpersonal communication effectiveness so that success is realized in achieving the goals of Pokdarwis Arumsari.